Quest and Response - Donald R. McCoy (1973)
Although the civilrights story of the Truman administration is one relating mainly to blacks, this study deals with other minority groups, including Indians, MexicanAmericans, Puerto Ricans, Japanese and ChineseAmericans, and Jews. Based on extensive research in primary source materials, it is a balanced, indepth analysis of the power of minorities in eliciting change. It is a valuable addition to the study of social as well as political history.